2007
DOI: 10.1177/1461444807080339
|View full text |Cite
|
Sign up to set email alerts
|

Relational quality and media use in interpersonal relationships

Abstract: Abstract:This study examined the relationship between relational quality and media use in interpersonal relationships. In addition, the impacts of other potentially important variables such as sex and relationship type of participants and their partners were explored. College student participants focused on interaction experiences with an acquaintance, friend, romantic partner, or family member. Questions addressed the sex of relational partners, how much of participants' total communication with relational pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
57
2
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(72 citation statements)
references
References 47 publications
(50 reference statements)
4
57
2
3
Order By: Relevance
“…For example, researchers found that mediated communication through telephone and the Internet neither improved nor detracted relational satisfaction and closeness [70]. Haythornthwaite [43] categorizes online exchanges as being as real as offline exchanges in terms of their impact on the tie and argues that it does not matter if the tie is maintained face-to-face or online, the relationship is what is important.…”
Section: New Media Use Patternsmentioning
confidence: 99%
“…For example, researchers found that mediated communication through telephone and the Internet neither improved nor detracted relational satisfaction and closeness [70]. Haythornthwaite [43] categorizes online exchanges as being as real as offline exchanges in terms of their impact on the tie and argues that it does not matter if the tie is maintained face-to-face or online, the relationship is what is important.…”
Section: New Media Use Patternsmentioning
confidence: 99%
“…Rice (2006) stated that women use the internet to get information about health more than men. Baym, Zhang, Kunkel, Ledbetter and Lin (2007) announced that women use the internet for the communication purpose more often than men.…”
Section: Resultsmentioning
confidence: 99%
“…They stated that both variables affect the use of the internet according to the data gained from 212 employees. Rice (2006) and Baym, Zhang Kunkel, Ledbetter and Lin (2007) stated that women use the internet more often than men in terms of the internet usage. Walter (2017) stated that different occupational groups might be affected differently by the use of ICT in the globalizing world.…”
Section: Importance Of the Internet For Employees And New Competenciementioning
confidence: 99%
“…SMT, therefore, creates virtual social space that aid and encourage various interactions among persons of the world: global networking. Baym et al, (2007)'s study found that because of so many people having busy lives or having friends and relatives in the Diaspora, these sites have helped to keep contact with those individuals that students rarely saw. The social networking is so much in use that the current debate is no longer on whether social networking should play a role in education but has shifted to what social networking tools work best and how to deploy them (Digital Directions, June 16, 2010).…”
Section: Introductionmentioning
confidence: 99%